Kaweng Turung: The Absence of State's Role in Harmful Marriage Tradition - Ahmad Rajafi; Ressi Susanti (Universitas Islam Negeri Jakarta, 2023)
This research discusses the practice of marriage in the Mongondow Muslim tradition in Indonesia, called kaweng turung. One of the problems in this tradition is related to the legal issue as, after the marriage contract, the husband must leave the wife without official divorce status. This study is based on fieldwork in Mongondow, North Sulawesi Province, involving interviews with the local leaders. It is found that the kaweng turung was not rooted in the ancient tradition of the Mongondow society. The practice has emerged currently as the result of globalization. The term kaweng turung comes from the daily dialect in Manado City. Despite the problem in its practice, the traditional institutions tend to passively follow it by formalizing the marriage. This study proposes that there is a need for a synergy between the State, the regional Ministry of Religious Affairs, and traditional institutions to prevent the practice of kaweng turung. One of the ways is through massive, systematic, and structured pre-marital education. Abstrak: Penelitian ini membahas tentang praktik perkawinan dalam tradisi Muslim Mongondow di Indonesia yang disebut kaweng turung. Salah satu permasalahan dalam tradisi ini adalah terkait masalah hukum, yaitu setelah akad nikah, suami harus meninggalkan istri tanpa status cerai resmi. Studi ini didasarkan pada kerja lapangan di Mongondow, Provinsi Sulawesi Utara, yang melibatkan wawancara dengan para pemimpin setempat. Penelitian in menmukan bahwa kaweng turung tidak berakar pada tradisi kuno masyarakat Mongondow. Praktik tersebut telah muncul saat ini sebagai akibat dari globalisasi. Istilah kaweng turung berasal dari dialek sehari-hari di Kota Manado. Terlepas dari masalah dalam praktiknya, lembaga adat cenderung pasif mengikutinya dengan meresmikan perkawinan. Kajian ini mengusulkan perlunya sinergi antara negara, Kementerian Agama di daerah, dan lembaga adat untuk mencegah praktik kaweng turung. Salah satunya melalui pendidikan pranikah yang masif, sistematis, dan terstruktur.